A longitudinal study assessing lens thickness changes in the eye of the growing beagle using ultrasound scanning: relevance to age of dogs in regulatory toxicology studies. Issue 12 (16th January 2014) - Maynard, Juliana; Sykes, Angela; Powell, Helen; Healing, Guy; Scott, Marietta; Holmes, Andrew; Ricketts, Sally‐Ann; Stewart, Jane; Davis, Stewart
ABSTRACT The lens is formed in utero with new secondary lens fibres added as outer layers throughout life in a growth pattern characteristic of the species. This study examined the time course of beagle lens growth to better understand the optimal starting age of dogs for safety studies to support adult versus paediatric indications, and to assess the feasibility of non‐invasively monitoring lens growth with high frequency ultrasound. Ultrasound scanning was performed in six female beagle dogs using the Vevo770. All dogs were imaged in B‐mode using local anaesthetic but without sedation. Imaging was carried out every 2 weeks from 8 to 22 weeks of age and then monthly until 62 weeks of age. The dogs tolerated the procedure well. The lens was visible in all dogs and measuring the lens thickness with high frequency ultrasound demonstrated good analytical reproducibility [Root Mean Square (RMS) = 3.13%]. No differences between the left and right eye existed and lens thickness correlated with body weight. The highest weekly growth rate was before 12 weeks of age. A statistically significant difference between monthly thickness was detected until 42 weeks of age at which point growth reached a plateau. During the experiment, lenses grew by 29.7% reaching an average thickness of 6.4 mm ± 0.03. By 10 months of age (the typical age used for routine toxicological evaluation), beagles have reached a plateau in lens growth that is analogous to human adults. Where lens is a target organ of concern it is suggested that beagles under 6 months old may be a better model for determining paediatric safety. Copyright © 2014 John Wiley & Sons, Ltd.